Complete remission of nonmetastatic persistent gestational trophoblastic tumour by Methotrexate and Actinomycin D: A case report - Shah, Bashant; Dangal , Ganesh; Karki , Aruna; Pradhan , Hema; Shrestha , Ranjana; Bhattachan , Kabin (Journal of Karnali Academy of Health Sciences, 2025)
Locally invasive non-metastatic persistent gestational trophoblastic tumours (PGTT) usually falls in low-risk group in WHO scoring system based on prognostic factors. We report a case of non-metastatic PGTT which followed a molar pregnancy. Complete remission of the tumour was achieved by 3 cycles of single agent chemotherapy (Methotrexate with leukovorin rescue) and 5 cycles of single agent (Actinomycin D).